2020
DOI: 10.1073/pnas.1922778117
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of age-related salivary gland autoimmunity by glycosylation-dependent galectin-1-driven immune inhibitory circuits

Abstract: Aging elicits quantitative and qualitative changes in different immune components, leading to disruption of tolerogenic circuits and development of autoimmune disorders. Galectin-1 (Gal1), an endogenous glycan-binding protein, has emerged as a regulator of immune cell homeostasis by shaping the fate of myeloid and lymphoid cells. Here, we demonstrate that aged Gal1-null mutant (Lgals1−/−) mice develop a spontaneous inflammatory process in salivary glands that resembles Sjögren’s syndrome. This spontaneous auto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 62 publications
6
31
0
Order By: Relevance
“…In particular, CD8 + IFNg + T and CD8 + PD-1 + T cell infiltration was higher. Consistent with the higher expression of CXCL9 and CXCL10 in submandibular glands, CD8 + CXCR3 + T cells' infiltration increased as well, compared with WT mice (36). It suggested that CTLs could be actively recruited into this target organ.…”
Section: Distribution Of Ctls In the Major Salivary Glandssupporting
confidence: 56%
“…In particular, CD8 + IFNg + T and CD8 + PD-1 + T cell infiltration was higher. Consistent with the higher expression of CXCL9 and CXCL10 in submandibular glands, CD8 + CXCR3 + T cells' infiltration increased as well, compared with WT mice (36). It suggested that CTLs could be actively recruited into this target organ.…”
Section: Distribution Of Ctls In the Major Salivary Glandssupporting
confidence: 56%
“…We demonstrated that aged Lgals1 -/mice had lower expression of PD-L1 in salivary gland cells and increased recruitment of IFN-γ-producing PD-1 + CD8 + T cells to this organ. Moreover, Gal-1-deficient mice showed higher frequency of DCs with immunogenic capacity [93]. We verified these findings in nonobese diabetic (NOD) mice, a well-established mouse model for Sjögren's-like syndrome.…”
Section: Sjögren's Syndromesupporting
confidence: 70%
“…Sjögren's syndrome is characterized by lymphocytic infiltration of exocrine glands and the presence of different autoantibodies. In contrast to CIA and EAE models, where mice were immunized with arthritogenic and encephalitogenic peptides, mice lacking Gal-1 or complex branched N-glycans developed spontaneous age-dependent sialadenitis resembling Sjögren's syndrome manifestations [93]. Lack of Gal-1 disrupted tolerogenic circuits and enhanced T cell activation and recruitment to the salivary glands.…”
Section: Sjögren's Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with this possibility, we observed the presence of a tolerogenic gene module of 30 genes, including IDO1 , LAMTOR1, IL4L1 and LGALS1, expressed by LCs. Galectin-1 encoded by the LGALS1 gene has been shown to promote the generation of tolerogenic DCs and to enable Tr1 type Tregs to supress Th1- and Th17-mediated inflammation 46,46 . Thus, Galectin-1 secreted by LCs could function in an autocrine as well as paracrine manner to promote Treg responses.…”
Section: Discussionmentioning
confidence: 99%